2015
DOI: 10.1001/jamadermatol.2014.3432
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Eczema and Stature in 9 US Population-Based Studies

Abstract: Eczema is not associated with short stature overall. However, a small subset of children and adolescents with severe eczema accompanied by prominent insufficient sleep may have potentially reversible vertical growth impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…The pooled prevalence of AD from all 19 surveys was 10·1% (95% CI, 10·0–10·2%). The sociodemographic associations of paediatric AD have been previously described …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled prevalence of AD from all 19 surveys was 10·1% (95% CI, 10·0–10·2%). The sociodemographic associations of paediatric AD have been previously described …”
Section: Resultsmentioning
confidence: 99%
“…The sociodemographic associations of paediatric AD have been previously described. 22 The U.S. pooled prevalence of ADD/ADHD was found to be 7Á3% (7Á2-7Á4%) in children. In bivariate logistic regression models, ADD/ADHD was associated with older age, lower household income, high school or 'general educational development' as highest level of household education (Supplementary Table S4; see Supporting Information).…”
Section: Prevalence Of Atopic Dermatitis and Attention Deficit (Hypermentioning
confidence: 98%
“…Previous studies found that sleep disturbances are a risk factor for headaches, as reviewed in previous studies. [12][13][14][15][16][17] Sleep disturbances in patients with eczema have recently been found to be associated with shorter stature 21 and poor health-related quality of life [22][23][24][25][26] in children and poorer overall health, 3 increased fractures and other injuries, 27 and even cardiovascular disease 28 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Intense pruritus, high rates of sleep disturbance, stigma, social isolation, poor quality of life, and neuro-inflammation have been postulated to contribute to increased anxiety, depression, or suicidality in AD. Sleep disturbances in AD were shown to be associated with a number of poor outcomes in AD patients, including headaches, 69 shorter stature in children, 70 poor QOL in children and adults, 5,13,14,71 increased fractures and other injuries, 72 and even cardiovascular risk factors or disease in adults. 73 Fatigue and sleep disturbances may increase the risk of, or share a common mechanism with, anxiety or depression.…”
Section: Mechanismmentioning
confidence: 99%